Different Mechanisms Must Be Considered to Explain the Increase in Hippocampal Neural Precursor Cell Proliferation by Physical Activity - Overall, Rupert W.; Walker, Tara L.; Fischer, Tim J.; Brandt, Moritz D.; Kempermann, Gerd (Frontiers in Neuroscience, 2016)
The number of proliferating neural precursor cells in the adult hippocampus is strongly increased by physical activity. The mechanisms through which this behavioral stimulus induces cell proliferation, however, are not yet understood. In fact, even the mode of proliferation of the stem and progenitor cells is not exactly known. Evidence exists for several mechanisms including cell cycle shortening, reduced cell death and stem cell recruitment, but as yet no model can account for all observations. An appreciation of how the cells proliferate, however, is crucial to our ability to model the neurogenic process and predict its behavior in response to pro-neurogenic stimuli. In a recent study, we addressed modulation of the cell cycle length as one possible mode of regulation of precursor cell proliferation in running mice. Our results indicated that the observed increase in number of proliferating cells could not be explained through a shortening of the cell cycle. We must therefore consider other mechanisms by which physical activity leads to enhanced precursor cell proliferation. Here we review the evidence for and against several different hypotheses and discuss the implications for future research in the field.